Discipline and Social Care Character Education Analysis in Class IV at Cilamajang State Elementary School - Rizka Aulia; Cece Rakhmat; Fajar Nugraha (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is motivated by the low character of discipline and social care possessed by fourth grade students at SDN Cilamajang. Of the 40 students, with 23 male students and 17 female students, 17 students obeyed the rules and 21 students disobeyed the rules. This study aims to determine the habituation of teachers at SDN Cilamajang in implementing disciplined and socially caring character education and to find out the supporting factors and inhibiting factors in habituating and implementing character education at SDN Cilamajang. The method used in this study is a qualitative method using observation, interview and documentation techniques. The subjects in this study were subjects based on student achievement, 2 high achievers, 2 moderate achievers and 2 low achievers with the assumption that they represented each student's characteristics. The results of this study state that the habit of teachers at SDN Cilamajang in implementing character education is carried out in daily habits. The inhibiting factor for the application of character education is discipline and social care, one of which is the habit of the teacher himself while the supporting factors are because it is a program of the curriculum so that the teacher is obliged to educate students in negative things. So it can be concluded that 3 out of 6 students have not been able to show good disciplinary character, and 1 out of 6 students have not been able to show good social care character. The family, school and community environment have the same obligation in implementing character education.